A Meta-Analysis of Adjuvant Therapy after Potentially Curative Treatment for Hepatocellular Carcinoma - Jun Wang; Xiao Dong He; Nan Yao; Wen Jia Liang; You Cheng Zhang (Canadian Journal of Gastroenterology)
BACKGROUND: The high recurrence rate of hepatocellular carcinoma (HCC) after potentially curative treatment determines the long-term prognosis.